Threshold concepts vs. Tricky topics: exploring the causes of student ́s misunderstandings with the problem distiller tool - Cruz, Sara Maria Alves (2016)
This paper presents a study developed within the international project JuxtaLearn. This project aims to improve student understanding of threshold concepts by promoting student curiosity and creativity through video creation. The math concept of 'Division', widely referred in the literature as problematic for students, was recognised as a 'Tricky Topic' by teachers with the support of the Tricky Topic Tool and the Problem Distiller tool, two apps developed under the JuxtaLearn project. The methodology was based on qualitative data collected through Think Aloud protocol from a group of teachers of a public Elementary school as they used these tools. Results show that the Problem Distiller tool fostered the teachers to reflect more deeply on the causes of the students’ misunderstandings of that complex math concept. This process enabled them to develop appropriate strategies to help the students overcome these misunderstandings. The results also suggest that the stumbling blocks associated to the Tricky Topic ‘Division’ are similar to the difficulties reported in the literature describing Threshold Concepts. This conclusion is the key issue discussed in this paper and a contribution to the state of the art.